Efficient Synthesis of Polyfunctionalized Pyrimidine Derivatives - Mahdavi, Mohammad; Kianfard, Hossein; Saeedi, Mina; Ranjbar, Parviz Rashidi; Shafiee, Abbas (Synlett, 2016)
A simple and direct procedure was developed for the synthesis of a novel series of polyfunctionalized pyrimidines. They were prepared via reaction of N-(substituted carbamothioyl)benzimidamides (prepared from the reaction of benzimidamide hydrochloride and isothiocyanates) and malononitrile in the presence of CuBr/Et3N in DMF at 80 °C.
Keywords: pyrimidines; heterocycles; isothiocyanates; malononitrile